AL-SULṬAH AL-TASYRI’IYYAH, AL-SULṬAH AL-TANFIẒIYYAH, AL-SULṬAH AL-QAḌᾹ’IYYAH - La Samsu (TAHKIM, 2018)
In Islam there is a division of power in three models. Al-sulṭah al-tasyri'iyah, is the power of the Islamic government in making and establishing the law. Al-Sulṭah al-Tanfiẓiyyah is the power to enforce the law on the ranks of the cabinet in a government. While al-Sulṭah al-Qaḍa'iyyah is a power that has a relationship with the duties and authority of the judiciary, which is guarding the monitoring the course of legislation by law enforcement. The three models of power are aimed at avoiding the centralization of power to only one ruler (authoritarian ruler).